2016
DOI: 10.4081/jae.2016.537
|View full text |Cite
|
Sign up to set email alerts
|

The influence of management and construction methods in the repair costs of Spain’s low-volume road network

Abstract: This paper describes the entire process of the implementation of the Spanish low volume road network, including the design criteria, the construction techniques and the management policies during all the periods. The current situation of low volume roads in Spain was analysed with respect to the legal framework and their actual condition. In addition, the budget required for the repair of 41 low volume roads throughout Spain was calculated in order to statistically analyse the influence of the pavement materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Removing the soft soil and replacing it with stronger material such as crushed rock or other recycled materials is well known as a technique to improve subgrade soils (Senol et al, 2006;Choudhary et al, 2010). In an investigation carried out in Spain, it was found that the utilisation several types of stabilised materials for low volume roads had a significant on repair costs due to durability (Gallego et al, 2016). There are many types of stabilised materials one of which is recycled material, which has been recently used in subgrade soil to replace traditional earth material for the purpose of environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Removing the soft soil and replacing it with stronger material such as crushed rock or other recycled materials is well known as a technique to improve subgrade soils (Senol et al, 2006;Choudhary et al, 2010). In an investigation carried out in Spain, it was found that the utilisation several types of stabilised materials for low volume roads had a significant on repair costs due to durability (Gallego et al, 2016). There are many types of stabilised materials one of which is recycled material, which has been recently used in subgrade soil to replace traditional earth material for the purpose of environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%